Malcolm X champion of equal rights - Abd Razak, Dzulkifli (2005)
excused for thinking that he is a new pop star who just came on the scene. Though a star in his own right, he is not from the entertainment industry. Malcolm was a revolutionary of the '50s and '60s, an AfricanAmerican with a social cause fighting what he saw as injustice against his people. Born as Malcolm Little on May 19, 1925 in the stat of Nebraska, US, Malcolm dropped his surname in preference of the alphabet X. This was a symbolic gesture that cut him off from his slavery past and he became a new voice to be heard. No matter how controversial it was, he preached messages of black pride and independence and championed civil rights. He was uneasy as an AfricanAmerican as seen in one of his quotes: "Sitting at the table doesn't make you a diner. Being here in American. Being born here in America doesn't make you and American.